Flipped classroom to promote active learning in statistics teaching - Rocha, Anabela (2024)
The flipped classroom model has emerged as a transformative approach in higher education, shifting the traditional teaching paradigm to enhance student engagement and learning outcomes. In this model, instructional content is delivered outside of class, often through video lectures, allowing in-class time to be devoted to active learning activities, such as discussions, problem-solving, and collaborative projects. Research indicates that the flipped classroom can improve academic performance, increase student motivation, and promote critical thinking skills. By leveraging technology and innovative teaching practices, the flipped classroom supports the development of teamwork, communication, and self-directed learning. Consequently, the adoption of the flipped classroom model in higher education holds significant potential for enhancing educational quality and preparing students for professional success. The flipped classroom model may be especially well-suited for introductory statistic courses in non maths degree programs, given the specific challenges of such courses, which are often required for students with widely varying mathematical skills and backgrounds Amalia et al. (2023), Kovacs et al. (2021). These students often exhibit low interest and high anxiety. Recent studies suggest the flipped classroom approach for introductory statistics courses can improve student performance compared to a traditional classroom settings Farmus et al. (2020). The authors implemented a flipped classroom model in the introductory statistics course of the Marketing Degree, aiming to increase student motivation and involvement, and to foster closer collaboration between students and the instructor, as well as among students themselves Baig and Yadegaridehkordi (2023). This study presents the outcomes and perceptions of this experience.